The humanistic organization in the complexity era - López-Casares Pertusa, Helena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The change in the digital and complex society requires the elaboration of a business philosophical framework adapted to the new paradigm of the 21st century The company is a modern institution of enormous influence and power an reveals itself as an agent of change, creator of realities, driver of innovation and catalyst of transformation and personal development. The new business cultures must focus on the person as source of advancement and progress. Humanism is the current that acquires meaning and protagonism to enhance the role of man and women in a fast, complex, uncertain, changing and turbulent context.